Does the application of whitening dentifrices during at-home bleaching affect the bond strength of resin composite to dentin? - Horieh Moosavi; Atefeh Nemati-Karimooy; Fatemeh Rezaei; Zahra Yavari; Farzaneh Ahrari (BMC, 2022)
Abstract Aim This study aimed to evaluate the effect of using whitening dentifrices during at-home bleaching on the shear bond strength (SBS) of resin composite to dentin, and investigate whether the increased polymerization time would improve SBS. Methods Ninety-six bovine incisors were divided into 4 groups of 24, according to the whitening treatment applied as follows: group 1, at-home bleaching + brushing with a regular dentifrice; group 2, at-home bleaching + brushing with a whitening dentifrice containing ozone; group 3, at-home bleaching + brushing with a commercial whitening dentifrice; and group 4 (control), no whitening/brushing treatment. Each group was divided into two subgroups (n = 12) to assess the effect of curing time (20 versus 80 s) on SBS. A self-etch adhesive was bonded to dentin, and after 2-day water storage, SBS was determined. Results SBS was significantly affected by the whitening treatment (P = 0.03), but increasing the curing time had no significant effect on SBS (P = 0.137). Bond strength in group 1 was comparable to the control group (P > 0.05). The specimens in group 3 displayed significantly lower SBS than either group 4 or group 1 (P > 0.05). No significant difference was observed between the SBS of group 2 compared to any other group (P > 0.05). There was no significant association between the treatment group and failure type (P > 0.05). Conclusion The bonding interface was not negatively influenced by the at-home bleaching procedure. However, using a commercial whitening dentifrice during at-home bleaching produced a significant detrimental effect on SBS. Extending the curing time would have no beneficial effect on adhesion to a whitened dental substrate.